Determinants of the Strength of Auditing and Reporting Standards: a Cross-Country Study - Pran Krishansing Boolaky; Chandrasekhar Krishnamurti; Ariful Hoque (Australasian Accounting, Business and Finance Journal, 2013)
Our study addresses the research gap regarding the absence of an empirical cross-country study on the determinants of the strength of auditing and reporting standards (SARS). Using data on 133 countries at various stages of development, we examine the role of environmental factors that influence a country’s strength of auditing and reporting standards. Our empirical results confirm that institutional infrastructure, financial market development and higher education and training jointly influence a country’s strength of auditing and reporting standards. We obtain qualitatively similar subsample results when we partition countries on the basis of economic development.
Keywords: Auditing; Reporting Standards; Development; Global